Detecção e identificação molecular de vírus associados a videiras sintomáticas e assintomáticas Molecular detection and identification of virus associated with symptomatic and symptomless grapevines - Marcos Fernando Basso; Thor Vinícius Martins Fajardo; Marcelo Eiras; Ricardo Antônio Ayub; Osmar Nickel (Ciência Rural, 2010)
A propagação vegetativa da videira favorece infecções virais múltiplas, com expressão diferencial de sintomas em função da combinação da cultivar ou espécie da hospedeira com a espécie viral. Os objetivos deste trabalho foram detectar e identificar as espécies virais presentes em duas espécies/cultivares de videira: uma sintomática e outra assintomática. DsRNA de ambas as amostras foi submetido à RT-PCR com 17 pares de oligonucleotídeos específicos para a detecção de Grapevine virus A (GVA), Grapevine virus B (GVB), Grapevine virus D (GVD), Grapevine fleck virus (GFkV), Grapevine fanleaf virus (GFLV), Arabis mosaic virus (ArMV), Grapevine chrome mosaic virus (GCMV), Rupestris stem pitting-associated virus (RSPaV), Grapevine leafroll-associated virus 1 a 4 (GLRaV-1 a -4), além de três pares de oligonucleotídeos degenerados. Pelo menos um fragmento amplificado, por par de oligonucleotídeos, foi clonado e sequenciado. Plantas sintomáticas e assintomáticas mostraram infecções múltiplas por RSPaV, GLRaV-2 e/ou GLRaV-3. As sequências de nucleotídeos obtidas para sete isolados de RSPaV, três de GLRaV-2 e dois de GLRaV-3 apresentaram identidades superiores a 90% com espécies homólogas e permitiram a definição das possíveis estirpes presentes nas amostras infectadas. Esses resultados evidenciam a necessidade da diagnose viral baseada em testes específicos para determinar a condição sanitária da videira. The vegetative propagation of grapevine facilitates multiple viral infections, with different symptoms which vary according to combinations of cultivar or host species with viral species. The aims of this research were to detect and identify the viral species infecting two grapevine species/cultivars: one symptomatic and one symptomless. DsRNA from both samples was assayed by RT-PCR using 17 pairs of specific primers for detection of the Grapevine virus A (GVA), Grapevine virus B (GVB), Grapevine virus D (GVD), Grapevine fleck virus (GFkV), Grapevine fanleaf virus (GFLV), Arabis mosaic virus (ArMV), Grapevine chrome mosaic virus (GCMV), Rupestris stem pitting-associated virus (RSPaV) and Grapevine leafroll-associated virus 1-4 (GLRaV-1 to -4), besides three degenerate primer pairs. For each primer pair at least one amplicon was cloned and sequenced. Symtomatic and symptomless plants were multiple infected by RSPaV, GLRaV-2 and/or GLRaV-3. The nucleotide sequences of seven isolates of RSPaV, three of GLRaV-2 and two of GLRaV-3 showed identities higher than 90% with the homologous viral species and allowed to identify possible viral strains in infected samples. These results highlight the necessity of viral diagnosis based on specific assays to determine grapevine sanitary status.